1971
DOI: 10.1017/s0043174500048682
|View full text |Cite
|
Sign up to set email alerts
|

Growth Characteristics of Common Milkweed

Abstract: Seed dormancy of common milkweed (Asclepias syriaca L.) is broken by a few days of moist low-temperature after-ripening. The duration of low-temperature after-ripening of the seeds is temperature dependent. Seedling emergence is best when the seeds are planted 1 to 2 cm deep and extremely limited when planted 6 cm deep. Seedlings have the capacity to produce new shoots if clipped in the 1 to 1¾-leaf pair stage and multiple shoots if clipped in the 2 to 2½-leaf pair stage. All seedlings reaching the 4 to 4½-lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Common milkweed seedlings have a greater range of emergence from coarse-textured soils (2,13). These results concur with prior research indicating maximum emergence of common milkweed occurs from the upper 0.5 to 2 cm of the soil profile and emergence is inhibited below 6 em (2, 19).…”
Section: Controlsupporting
confidence: 88%
“…Common milkweed seedlings have a greater range of emergence from coarse-textured soils (2,13). These results concur with prior research indicating maximum emergence of common milkweed occurs from the upper 0.5 to 2 cm of the soil profile and emergence is inhibited below 6 em (2, 19).…”
Section: Controlsupporting
confidence: 88%
“…Each seed was gently pushed down to approximately 3 cm below the surface to avoid further dispersion and thus the invasion of other plots. This depth allowed for having even the biggest seeds of Cenchrus covered with 1-1.5 cm layer of soil, but it was near or within the range of ideal burial depth for all other species as well [Kowarik and Säumel (2007) for Ailanthus, Jeffery and Robison (1971) for Asclepias and Guillemin and Chauvel (2011) for Ambrosia].…”
Section: Experimental Designmentioning
confidence: 98%
“…Bhowmik and Bandeen found that common milkweed was able to produce buds on the root 18 to 21 days after emergence. 5 Jeffery and Robison (8) found that 5% of the common milkweed seedlings clipped when 2 to 3 cm in height resprouted. When clipped at the 7.5 to 12.0 cm height, 100% resprouted.…”
Section: Germination Rate Indexmentioning
confidence: 99%